IDDF2018-ABS-0233 N6-adenosine methyltransferase METTL3 promotes tumour metastasis via SOX2 MRNA M6A modification in colorectal carcinoma. (June 2018) - Li, Ting; Hu, Peishan; Zuo, Zhixiang; Ju, Huaiqiang
Abstract : Background: Colorectal carcinoma(CRC) is one of the most common malignant tumours, which main cause of death is tumour metastasis. The role of METTL3 (N6-adenosine-methyltransferase 70 kDa subunit) in cancer has not been well studied. This study reveals a new role of METTL3 in promoting CRC tumour progress through m6A modification of SOX2 (SRY-box 2) and influencing the Epithelial-Mesenchymal Transition process. Methods: Western blot and Immunohistochemistry were used to detect METTL3 expression in cell lines and patient's tissues. The MTS assay, invasion assay, sphere formation assay was performed to detect the function of METTL3. Cell based xenograft model and PDX model revealed the clinical benefits of target METTL3 in vivo . Transcriptome sequencing and uencing were used to screen the m6A target genes, and MeRIP qPCR was used to detect the m6A level of the target gene. Results: Using TCGA database, we found that METTL3 was significantly upregulated in human CRC and high expression of METTL3 in metastasis CRC was associated with poor prognosis of patients. Knockdown of METTL3 in CRC sample cell line and SW620 dramatically suppressed cellular proliferation, migration and sphere formation in vitro. METTL3 inhibition suppresses CRC tumorigenesis and metastasis in both cell models and PDX models in vivo . Mechanistically, we performed RNA-sequencing and MeRIP- sequencing in SW480 and SW620 CRC cell lines and SOX2 was identified as the target of METTL3-mediated m6A modification. The protein level, m6a modification level, and RNA stability of SOX2 was significantly decreased upon METTL3 inhibition. Comparing with the m6a-site-mutant SOX2, only the wildtype modified SOX2 promoting tumour progress through activating EMT process. The RNA and protein level of SOX2 downstream genes were dramatically diminished after METTL3 knockdown and both SOX2 and its target genes showed a positive correlation with METTL3 expression in CRC patients. Conclusions: In summary, we demonstrated that METTL3, acting as an oncogene, was frequently upregulated in human CRC and contributed to CRC metastasis. METTL3 maintained SOX2 expression to activate EMT process through the m6A dependent mechanism. Thus, our findings reveal an important role of METTL3 and provide a potential target of treatment in colorectal carcinoma.